: English - Ramachandran, Jonathan (QUAERENS: Journal of Theology and Christianity Studies, 2025)
This paper proposes that the verses found in 1 Thessalonians 4:17 and 1 Corinthians 15:52 describe two distinct prophetic events that are separated by a thousand-year period. The interpretation is not built merely on surface-level readings of the texts, but rather draws from the consistent implications within the writings of the earliest Church fathers—particularly those aligned with the Chiliasm model. These writings are compared with modern interpretations to identify points of doctrinal continuity and divergence. Each Church father quotation is examined closely, with attention given to the context and detail of their statements. Common objections to Chiliasm are addressed directly. The framework for this interpretation rests on the prophetic model of Chiliasm, which affirms a literal one-thousand-year reign of Christ on earth prior to the final state. The roles and distinctions of these two verses are made clearer through patristic evidence, and interpolations are offered to explain why such a gap must exist. If valid, this study may serve as a rediscovery of a lost interpretive tradition—what one might call prophetic archaeology in analogy to traditional archaeology. The article argues that 1 Thessalonians 4:17 and 1 Corinthians 15:52 describe two distinct prophetic events separated by a thousand-year period, based on interpretations from Chiliasm Church Fathers.